Positive Solutions to a Coupled Fractional Differential System with p-Laplacian Operator. (17th June 2019) - Liu, Yuehan; Zhao, Xiaodi; Pang, Huihui
Abstract : In this paper, we consider a fractional differential system with multistrip and multipoint mixed boundary conditions involvingp -Laplacian operator and fractional derivatives. The existence result of positive solutions is established by the Leggett-Williams fixed point theorem. Also, an example is presented to illustrate our main result.